2013
DOI: 10.1063/1.4775782
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Theoretical prediction of the structure and spectroscopic properties of the $\tilde{\mathrm{X}}$X̃ and $\tilde{\mathrm{A}}$Ã states of hydroxymethyl peroxy (HOCH2OO) radical

Abstract: The hydroxymethyl peroxy (HMOO) radical is a radical product from the oxidation of non-methane hydrocarbons. The present study provides theoretical prediction of critical spectroscopic features of this radical that should aid in its experimental characterization. Structure, rotational constants, and harmonic frequencies are presented for the ground and first excited electronic states of HMOO. The adiabatic transition energy for the \documentclass[12pt]{minimal}\begin{document}$\tilde{\mathrm{A}} \leftarrow \ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Prior experimental investigations of the ground-state vibrational transitions -either in the gas phase [11,17,18] or within an inert matrix [19,20] -have aided in these assignments. Theoretical work has also helped to disentangle the complex spectra of the ground and first excited states [8,[21][22][23][24][25][26][27][28][29][30][31][32][33], but relatively few high-level ab initio studies are available; many have been limited to HO 2 [3,19,[34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 98%
“…Prior experimental investigations of the ground-state vibrational transitions -either in the gas phase [11,17,18] or within an inert matrix [19,20] -have aided in these assignments. Theoretical work has also helped to disentangle the complex spectra of the ground and first excited states [8,[21][22][23][24][25][26][27][28][29][30][31][32][33], but relatively few high-level ab initio studies are available; many have been limited to HO 2 [3,19,[34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 98%
“…Very recently, calculation on the structure and the spectroscopy of the peroxy radicals have been performed by Delcey et al. . Formation of the hydroxy‐methyl radical from HO 2 + CH 2 O has been verified by direct detection of the vibrational and electronic spectra using infrared and near‐infrared cavity Ringdown spectroscopy , though no kinetics of the reaction was reported.…”
Section: Introductionmentioning
confidence: 99%
“…After the submission of this manuscript, Delcey et al reported high-level calculations of both the X̃ and à states of HMP, computed at the CASPT2 and RCCSD(T) levels of theory. The more accurate RCCSD(T) calculations provide values for the adiabatic transition energy of T 0 = 7360 cm –1 , in excellent agreement with those observed here.…”
mentioning
confidence: 99%